La cura della malattia mentale: il lavoro terapeutico di gruppo e la psicoterapia di gruppo - Stocco, Ester (Il sogno della farfalla, 2018)
The article describes how group psychotherapy and group rehabilitation activities have been used to treat some mental illnesses. After describing how intermediate psychiatry rehabilitation infrastructures were born in Italy and what their role was, the author focuses on what has been carried out within a daily mental unit and a few intermediate infrastructures, i.e. therapeutic communities and residential communities, of a Mental Health Department in Rome. There, since 1995, a unique treatment for both acute and chronic psychosis has been carried out. The fundaments of this approach are Human Birth Theory by Massimo Fagioli and the education each of the psychotherapists received at the seminars of Analisi collettiva. The article shows how, over the years, all the operators of these infrastructures have been involved in the search for an operative and effective model aimed at avoiding isolation, the lack of affectivity and dissociation, which are typical of psychosis. The efficacy of such a therapeutic model lies in the perseverance, regularity, coherence, professionalism and the aptitude of the operators to relating to others.